Determinants of Internal Auditor’s Ability in Detecting Fraud with Supervision as Moderating Variable - Defel Septian; Widia Febrianti (JAFFA, 2022)
This study examines the effect of independence, time pressure, and workload on the ability of the Central Java Inspectorate auditor to detect fraud with supervision as a moderating variable. This study used 31 internal auditors of the Central Java Inspectorate Apparatus as the sample, determined based on census sampling. This study’s results indicate a positive influence between independence and the ability of auditors to detect fraud. Variables time pressure and workload suggest that there is a negative influence on the capability of auditors to detect fraud. The interaction between supervision with independence cannotstrengthen the ability of auditors to detect fraud. Interaction of supervision with time pressure and workload cannot weaken the ability of auditors to detect fraud. The government must recruit more Inspectorate Apparatuses in Central Java to mitigate time pressure and workload, so the auditor can detect fraud better.